La necesidad de apreciar historias dentro de las teorías sobre necesidades humanas (The need to appreciate stories within theories of human needs) - Lozano Treviño, David Fernando; Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración, 2015)
Abstract: This paper presents the needs to apreciate stories that people have. Abraham Maslow´s hierarchy of needs is analyzed as well as the theories proposed by Alderfer, motivational-hygiene, expectations, equity theory, McClelland´s and the needs of Henry Murray. It reflects on the human needs of information and why this is generated. The issue of how the Film Production Organizations exploits the spectatores desires to appreciate stories and how those companies try to satisfy these needs. Narrative factors that are used by film organisations in movies and tv series production is studied. Finally, it briefly shows the substance, structure, style and principles of the successful movies and tv series stories, according to McKee.